The United States Department of Commerce; a story of industry, science, and trade. - Terrell, John Upton, 1900- (Duell, Sloan and Pearce, 1966)
Describes the work of the Department of Commerce in the following areas: shipping, patents, weather, roads, depressed areas, navigation, measurement, and business.